The Study of Religious Pluralism In The View of the Qur'an: Thematic Interpretation Approach - Zaenal Abidin (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2021)
Pluralism is one study that is often of concern to various intellectual circles; Both Muslim scholars and orientalism. The various views that are